2019
DOI: 10.3897/natureconservation.34.30720
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton temporal dynamics in the coastal waters of the north-eastern Adriatic Sea (Mediterranean Sea) from 2010 to 2017

Abstract: Phytoplankton community structure was analysed from 2010 to 2017 at C1-LTER, the coastal Long-Term Ecological Research station located in the Gulf of Trieste, which is the northernmost part of the Mediterranean Sea. Phytoplankton abundance and relevant oceanographic parameters were measured monthly in order to describe the seasonal cycle and interannual variability of the main phytoplankton taxa (diatoms, dinoflagellates, coccolithophores and flagellates) and to analyse their relationship with environmental co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 65 publications
4
33
0
Order By: Relevance
“…This was not in accordance with the results of Cetinić et al [4], who found the spring characterised by the highest phytoplankton abundance. In the Northern Adriatic, the spring peak was dominated by nanoflagellates and small diatoms, and a second slight increase in autumn was dominated by nanoflagellates, larger diatoms, and coccolithophores, as observed by Cerino et al [29].…”
Section: Phytoplankton Communitysupporting
confidence: 59%
“…This was not in accordance with the results of Cetinić et al [4], who found the spring characterised by the highest phytoplankton abundance. In the Northern Adriatic, the spring peak was dominated by nanoflagellates and small diatoms, and a second slight increase in autumn was dominated by nanoflagellates, larger diatoms, and coccolithophores, as observed by Cerino et al [29].…”
Section: Phytoplankton Communitysupporting
confidence: 59%
“…The two sites in the Gulf of Trieste do not differ significantly in terms of substrata and exposure to winds and currents, since both can be defined as "rocky shallow moderately exposed" [56]. However, the Miramare MPA is located in an area that is subject to high nutrient availability in the spring and autumn periods due to riverine discharges, especially from the Isonzo River [76], while the Piran site is influenced mainly by smaller rivers [77]. Thus, we can assume that it is less eutrophic in general, even if nutrient data are not collected from such shallow waters, but at a distance of 1.3 km from the coast [77].…”
Section: Discussionmentioning
confidence: 99%
“…In the northern Adriatic ecosystems and the GoT area, a review of numerous long term studies on river discharg, oceanographic features, plankton, fish and benthic compartments, collected since the 1970s revealed significant changes in mechanisms and trophic structures [53,73]. In detail, a gradual increase in eutrophication phenomena, characterized by significant hypoxic events at the bottom, was recorded during the 1970s until the mid-1980s [74,75,76], followed by a reversal of the trend, particularly marked in the 2000s [66,77]. This trend was attributed to a combination of the reduction in anthropogenic impact, mainly due to a substantial decrease of the phosphorus loads, and of climatic modifications, resulting in the decline in atmospheric precipitations and, consequently, of runoff [78,79].…”
Section: Discussionmentioning
confidence: 99%